Short Communication: Floristic survey of vascular plant in the submontane forest of Mt. Burangrang Nature Reserve, West Java, Indonesia - TRI CAHYANTO; muhammad Efendi; RICKY MUSHOFFA SHOFARA; MUNA DZAKIYYAH; NURLAELA; PRIMA G. SATRIA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Cahyanto T, Efendi M, Shofara RM. 2019. Short Communication: Floristic survey of vascular plant in the submontane forest of Mt. Burangrang Nature Reserve, West Java, Indonesia. Biodiversitas 20: 2197-2205. A floristic survey was conducted in submontane forest of Block Pulus ??Mount Burangrang West Java. The objectives of the study were to inventory vascular plant and do quantitative measurements of floristic composition as well as their structure vegetation in the submontane forest of Nature Reserves Mt. Burangrang, Purwakarta West Java. Samples were recorded using exploration methods, in the hiking traill of Mt. Burangrang, from 946 to 1110 m asl. Vegetation analysis was done using sampling plots methods, with plot size of 500 m2 in four locations. Result was that 208 species of vascular plant consisting of basal family of angiosperm (1 species), magnoliids (21 species), monocots (33 species), eudicots (1 species), superrosids (1 species), rosids (74 species), superasterids (5 species), and asterids (47), added with 25 species of pterydophytes were found in the area. The three families of plants are Lauraceae (10 species), Urticaceae (9 species), and Rubiaceae (8 species) dominating those areas. Fourteen species belong to IUCN red list: Least concern/LC (12 species), Vulnerable/VU (1 species), and endangered/EN (1 species). Furthermore, Castanopsis argentea A.DC, Pinanga javana Blume and Amorphophallus decus-silvae Backer & Aldrew belonging to protected plants are also found in the area. Based on the assessment of analysis vegetation, the forest has experienced disturbance, the density of trees is commonly  low and has a lot of gaps. Many vacant lots are found. On the other side, there is the presence of invasive plant species that may slow down a succession into climax growth of local plant.